Marketing Strategy for Cibaduyut SME'S Craftsmen Post Covid 19 Pandemics - Ayu Widia; Rizqi Muttaqin; Denny Saputera (PT Inovasi Pratama Internasional, 2023)
This article describes and explores the function and role of the UMKM shoemaker’s producer of marketing strategy at Cibaduyut area on the latest endemic condition post Covid 19. The objective article is to define what is the influence of the marketing strategy that UMKM in Cibaduyut did before, during and after Covid-19 pandemic that already going into endemic on their daily activity at shoemaker's producer operation and the struggles of these UMKM in applying the digitalization marketing to their business operation in purpose of maintain performance during and after the Covid 19. The method for this article used was qualitative methods through observations, interviews and study trip with literature and data processed. This article indications that shoemaker’s producer’s challenges are in using digital platforms and offers alternatives to improve the formulation of marketing strategies for UMKM to apply digital platforms in their business operations to be more efficiently and successfully applied to face the post Covid-19 Pandemic and adapt the new normal situation.